البعد القانوني للحدود الفاصلة بين الغلط والخطأ الموجبان للمسؤولية الطبية لمهنيي الصحة: دراسة تحليلية للأحكام القضائية الفرنسية والأحكام القضائية في دولة الإمارات العربية المتحدة - الافتيحات، ياسر عبدالحميد محمد Alaftihat, Yasser Abdulhamid Mohammed (جامعة البحرين - كلية الحقوق, 2020)
ترتبط مهنة الطب بالسلامة الجسدية المباشرة للمريض، وما أتى تدخل مهنيي الصحة إلا لإعادة الحالة إلى ما كانت عليه أو لتخفيف الألم، لذا بقي الأصل في التزامات مهنيي الصحة هو التزام ببذل عناية، ولا يعني ذلك لا مسؤولية طبية عليهم حال ارتكابهم للخطأ الذي يعد حجر الأساس لتحققها. ولأجل ممارسة نشاطهم بصورة عفوية بعيدا عن الريبة والخوف من نشوء المسؤولية الطبية، يلزم تحديد ماهية الخطأ فليس كل فعل سبب ضررا قبل أو خلال أو بعد ممارسة النشاط الطبي على المريض سينعت بالخطأ بل لابد من وجود هامش للغلط الذي في الأصل يعد أمراً طبيعياً غير موجب للمسؤولية الطبية. والسؤال الأهم هل هناك مجال للحديث عن الغلط فضلاً عن الخطأ من ممارسة الطبيب لعمليات التجميل التي يفترض أن يكون التزام الطبيب بنتيجة وليس ببذل عناية وعندها لا مجال للحديث عن الخطأ فضلاً عن الغلط. وعليه سيكون الغلط محور حديثنا لمعرفة هل هو مرادف للخطأ أو مستقل عنه؟ حيث يلزم أن تتضح للطبيب ولفريقه أثناء التدخل الطبي صورة متكاملة عن الخطأ الطبي الموجب للمسؤولية الطبية، وأين موقع الغلط من ذلك كله. ولكي تكون دراستنا هادفة محققة لهذه الغاية فإن نقطة الارتكاز ستكون: قانون المسؤولية الطبية رقم ٤ لسنة ٢٠١٦ الاتحادي، وتحليل الأحكام القضائية في المحاكم الاتحادية ومحاكم التمييز في الإمارات مع مقارنتها بالأحكام القضائية الفرنسية.
The medical profession is linked to the patient's direct physical safety, and the purpose of intervention of health professionals is to bring the situation back to its level or to relieve pain. Therefore, the essence of health professionals’ obligation is an obligation of means, but that doesn’t mean there’s no medical liability for the doctors when they commit a fault, which is considered the cornerstone for confirming medical liability. For doctors to carry out their activity spontaneously away from anxiety and fear of medical liability, it is necessary to define and understand the fault because the latter is not any act causing damage; before, during, or after the exercise of the medical activity, but there must be a probability of the error, which is considered natural and excludes medical liability. The most important question is whether there is room to consider the error as well as the mistake from the doctor's practice of cosmetics surgeries that are supposed to be the doctor's obligation of result, not an obligation of means. In this case, we cannot talk about mistake rather than error. Therefore, error will be the focus of our discussion to see whether it is synonymous with mistake or independent of it. The doctor and his team must be aware of the facts and principles of mistakes requiring medical liability and the place of error over mistake. For an objective approach, we will refer to the Federal Medical Liability Act No. 4 of 2016 and the analysis of judicial decisions in the Federal Courts and Courts of Appeal in the United Arab Emirates compared to French courts.
Keywords: القوانين والتشريعات -- المسؤولية القانونية الطبية -- المهن الصحية -- فرنسا -- الإمارات